THE EFFECTS OF JIGSAW READING TECHNIQUE UPON THE ACHIEVEMENT OF READING COMPREHENSION - Hanna Sundari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2011)
This is an experimental study that has significances of research as follow: (1) to get an empirical data and analyze the achievement of reading comprehension using jigsaw reading technique, (2) to get an empirical data and analyze the achievement of reading comprehension using conventional technique, (3) to analyze the different effects from teaching using jigsaw reading technique to conventional technique upon the achievement of reading comprehension. Jigsaw reading technique is technique of cooperative learning that assigned the students in groups to put pieces of material together. They first form home-team, and then join expert-team, after that return to home-team to discuss the material given.Keywords: Jigsaw reading technique, achievement of reading comprehension